2014
DOI: 10.3389/fimmu.2014.00517
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Free Light Chains and GAGs Mediate Multiple Myeloma Extracellular Vesicles Uptake and Secondary NfκB Nuclear Translocation

Abstract: Multiple myeloma (MM) is a hematological malignancy caused by a microenviromentally aided persistence of plasma cells in the bone marrow. Monoclonal plasma cells often secrete high amounts of immunoglobulin free light chains (FLCs) that could induce tissue damage. Recently, we showed that FLCs are internalized in endothelial and myocardial cell lines and secreted in extracellular vesicles (EVs). MM serum derived EVs presented phenotypic differences if compared with monoclonal gammopathy of undetermined signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 38 publications
5
48
0
Order By: Relevance
“…Moreover, heparin has been shown to directly interact with extracellular vesicles and heparin inhibits vesicle binding to target cells (11,14). In another study, exogenous heparin or treatment of cells with heparan sulfate degrading enzymes reduced exosome-target cell interaction by ϳ50% (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, heparin has been shown to directly interact with extracellular vesicles and heparin inhibits vesicle binding to target cells (11,14). In another study, exogenous heparin or treatment of cells with heparan sulfate degrading enzymes reduced exosome-target cell interaction by ϳ50% (12).…”
Section: Discussionmentioning
confidence: 99%
“…Although the functional effects of exosomes rely on their interaction with, and subsequent delivery of their cargo to target cells, the mechanisms mediating exosome-cell interactions remain unclear. Studies have shown that heparin can block interactions between extracellular vesicles and cells and that heparan sulfate proteoglycans on glioblastoma cells facilitates extracellular vesicle uptake (11)(12)(13)(14). This uptake was blocked by the addition of exogenous heparin (a highly sulfated glycosaminoglycan mimetic of heparan sulfate), which can compete with cell surface heparan sulfate to bind exosomes.…”
mentioning
confidence: 99%
“…Ten mL of serum free RPMI 1640, supplemented with 1% penicillin/streptomycin and 1% glutamine, was added to each plate. A serial centrifugation protocol previously described [21] was used to isolate EVs produced by 2 × 10 7 cells from serum free medium, after 24 h incubation. The quantity of isolated EVs obtained by serum-free culture medium is greatly increased while retaining EV biophysical and size properties [22].…”
Section: Extracellular Vesicles Separation and Characterizationmentioning
confidence: 99%
“…through the measurement of their acetylcholinesterase activity. The highest EV amount was found in MM patients in contrast to healthy donors and patients with monoclonal gammopathy of undetermined significance (MGUS) [112]. Moreover, exosome secretion from MM cells was shown to be dramatically increased by heparanase whose expression is up-regulated in aggressive cancer cells including MM cells, implying that heparanase may be one of the factors causing elevated secretion of exosomes [113].…”
Section: Evs In MMmentioning
confidence: 99%
“…Umezu et al [88] found that MM cells under hypoxic conditions secreted more exosomes with increased levels of miR-135b which induced increased expression of HIF-1α in endothelial cells, leading to enhanced angiogenesis. Moreover, serum EVs obtained from MM patients clearly promoted the proliferation of human vascular endothelial cells as compared to those from healthy donors or MGUS patients [112]. A very recent paper has suggested that fibronectin on the surface of MM cell-derived exosomes binds to heparin sulfate on endothelial cells thereby mediating MM exosome-BM cell interactions [131].…”
Section: Evs In MMmentioning
confidence: 99%